Spectrophotometric Absorption Correction Methods for the Estimation of Fixed-Dose Combinations of Dapagliflozin and Metformin Hydrochloride - Dalal, Deepak; Kant, Ravi; Attri, Kavita; Sharma, Kiran; Dhanawat, Meenakshi (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: For the assessment of fixed-dose combinations of Dapagliflozin and Metformin Hydrochloride in bulk pharmaceuticals and pharmaceutical formulations utilizing distilled water as a solvent, a novel, straightforward, precise, and accurate UV-spectrophotometric absorbance correction approach was devised. On the additive absorbance property, an absorbance correction method was based. Materials and Methods: By keeping Dapagliflozin and Metformin hydrochloride apart, a distinct spectrum was generated, displaying absorption maxima peaks (max) at 275nm (DAPA), and 245nm (MET). Compared to metformin hydrochloride, dapagliflozin displayed some absorbance at 275nm. At 245nm, both drugs exhibit absorption. A method for solving equations is based on measuring the absorbance of two wavelengths, 275nm, and 245nm. Exactly validating the procedure was done. Dapagliflozin and metformin hydrochloride concentration ranges of 2–10 μg/mL and 20–100 μg/mL, respectively, were used in the assays utilizing the absorbance correction method at 275nm and 245nm, respectively. Results: The mean recovery for each compound was 100.25 + 0.0459% and 99.82 + 0.059. The accuracy (RSD 2%) was discovered to be within bounds. This approach had precise and accurate optical properties. The proposed method can be used with pharmaceutical formulations, and it was unaffected by the usual excipients included in the formulation. Conclusion: The findings demonstrate that the method is practical for routine estimation of the fixed-dose combination of dapagliflozin and metformin hydrochloride, in a pharmaceutical dosage form. It is straightforward, conscious, accurate, and applicable.
Keywords: Dapagliflozin; Metformin hydrochloride; Absorbance correction method; Method; validation